Equestrian Activities for Character Building in Islamic Boarding Schools: Insights from Imam Bukhari Pesantren within the SDGs Framework - Raditya Rahmahadikusuma; Ataollah Rahmani (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study examines the role of character education embedded in equestrian extracurricular activities at the Imam Bukhari Islamic Boarding School, Karanganyar, Central Java, and analyzes how such activities function as an effective medium for shaping students’ personality values and noble morals. The main objective is to explore the contribution of horseback riding programs to holistic character formation within the context of Islamic education, while also aligning these practices with the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), and SDG 16 (Peace, Justice, and Strong Institutions). Theoretical framework: The theoretical framework is grounded in Islamic character education theory, which emphasizes the cultivation of akhlaq, ethics, spirituality, and physical discipline through practical activities rooted in the sunnah, including equestrian practices. Literature review: The literature review discusses Islamic perspectives on character education, the urgency of physical activity in personality development, and the pedagogical values of equestrian traditions as part of non-formal education in pesantren. Methods: Methodologically, this research employs a qualitative approach using a case study design. Data were collected through participant observation, in-depth interviews with coaches and students, and documentation of training programs and institutional policies related to extracurricular activities. Results: The findings reveal that systematically implemented equestrian activities effectively integrate key character values such as discipline, responsibility, courage, patience, cooperation, and self-control. Coaches play a dual role as technical instructors and moral educators, consciously embedding Islamic teachings and ethical reflection into training sessions. Students actively involved in equestrian programs demonstrate positive changes in behavior, learning motivation, emotional resilience, and social interaction, supporting both educational quality and student well-being. Implications: The implications of this study highlight the strategic importance of designing extracurricular curricula based on Islamic character values to strengthen holistic education in Islamic boarding schools and to contribute to SDG-oriented educational practices. Novelty: The novelty of this research lies in its empirical demonstration of equestrian activities as an effective, sunnah-based medium for character education, a topic that remains underexplored in contemporary pesantren studies.